A pH‐Based Pedotransfer Function for Scaling Saturated Hydraulic Conductivity Reduction: Improved Estimation of Hydraulic Dynamics in HYDRUS - Ali, A. (2020)
A nonlinear pedotransfer function was also produced, using the Levenberg–Marquardt optimization algorithm, by considering the pH and electrolyte concentration of the applied solution as well as the soil clay content. This approach improved the estimation of the pH scaling factor relating to Ks reduction for individual soils. The functions were based on Ks reduction in nine contrasting Australian soils using two sets of treatment solutions with Na adsorption ratios of 20 and 40; total electrolyte concentrations of 8, 15, 25, 50, 100, 250, and 500 mmolc L−1; and pH values of 6, 7, 8, and 9. A comparison of the experimental data and model outputs indicates that the models performed objectively well and successfully described the Ks reduction due to the pH. Further, a nonlinear function provided greater accuracy than the generalized function for the individual soils of Australia and California. This indicates that the nonlinear model provides an improved estimation of the pH scaling factor for Ks reduction in specific soils in the HYDRUS model and should therefore be considered in future HYDRUS developments and applications.